Oncological outcome after hyperthermic isolated limb perfusion for primarily unresectable versus locally recurrent soft tissue sarcoma of extremities - Vassos, Nikolaos; Brunner, Maximilian; Perrakis, Aristotelis; Göhl, Jonas; Grützmann, Robert; Hohenberger, Werner; Croner, Roland (Surgical oncology, 2020)
Introduction - The management of locally advanced extremity soft tissue sarcomas, particularly in terms of a limb salvage strategy, represents a challenge, especially in recurrent tumors. In the context of a patient-tailored multimodal therapy, hyperthermic isolated limb perfusion (ILP) is a promising limb-saving treatment option. We report the outcome of patients with primarily irresectable and locally recurrent soft tissue sarcoma (STS) treated by ILP. - Patients and methods - Data about patient demographics, clinical und histopathological characteristics, tumor response, morbidity and oncological outcome of all patients with STS, who underwent an ILP at our institution in a 10-year period, were retrospectively detected and analyzed. - Results - The cohort comprised 30 patients. Two patients were treated with ILP for palliative tumor control, 13 patients because of a local recurrent soft tissue sarcoma (rSTS) and 15 patients because of primarily unresectable soft tissue sarcoma (puSTS). 25 of the 28 patients with curative intention received surgery after ILP (11 pts with rSTS and 14 pts with puSTS). Histopathologically we observed complete response in 6 patients (24%) and partial responses in 19 patients (76%) with a significant better remission in patients with puSTS (p = 0,043). Limb salvage rate was 75%. Mean follow-up was 69 months [range 13-142 months]. Seven (7/11; 64%) patients with rSTS and one (1/14; 7%) patient with puSTS developed local recurrence after ILP and surgery, whereas eight (8/13; 62%) rSTS patients and seven (7/15; 47%) puSTS patients developed distant metastasis. During follow-up, eight patients (28.5%) died of disease (5/13; 38%) rSTS and 3/15 (20%) puSTS. ILP in the group of previously irradiated sarcoma patients (n = 13) resulted in a limb salvage rate of 69% and was not associated in an increased risk for adverse events. - Discussion - ILP for advanced extremity STS is a treatment option for both puSTS and rSTS resulting in good local control and should be considered in multimodal management. ILP is also a good option for patients after radiation history.
Gesehen am 19.07.2024